A new species of Osteobrama (Teleostei: Cyprinidae) from the Mahanadi River, India with a note on the validity of O. dayi - Shangningam, Bungdon; Rath, Shibananda; Tudu, Asha Kiran; Kosygin, Laishram (Zootaxa, 2020)
A new species of the genus Osteobrama is described from the Mahanadi River, Tikarpada, Angul District, Odisha state, India. Osteobrama tikarpadaensis, new species, differs from its congeners in having two pairs of minute barbels; iii–iv unbranched dorsal-fin rays with 25–33 serrae on the last unbranched ray; 15–16 branched pectoral-fin rays, and 25–27 branched anal-fin rays. The status of Osteobrama dayi is discussed and shown to be a valid species. A key to the species of the genus is provided.